A low-warp ultra-high performance lithium battery copper foil and a preparation method and application thereof

CN122992087APending Publication Date: 2026-10-27JIUJIANG TELFORD ELECTRONICS MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510712025.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-29
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]常规铜箔一方面由于翘曲高,物性低,如翘曲>10mm,抗拉强度在300-500MPa,其中翘曲高会影响到负极活性材料涂覆均匀性及结合性,且易打折;抗拉强度过低容易出现断带,影响制程效率

Benefits of technology

(1)提高极片制程效率:本发明的低翘曲超高性能锂电铜箔能有效降低极片打折和断带风险,提高极片制程效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present application relates to a kind of low warping ultra-high performance lithium copper foil and its preparation method and application, the copper foil includes smooth surface and rough surface, the warping direction of copper foil is smooth surface towards rough surface, warping degree <10 mm.The copper foil of the present application can effectively reduce the risk of pole piece folding and broken strip, improve the efficiency of pole piece process;Can resist the high temperature and volume change generated in the process of cyclic charge and discharge of battery, maintain stable physical properties, thereby improve the thermal stability of battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium battery technology, and specifically relates to a low-warpage ultra-high performance lithium battery copper foil, its preparation method, and its application. Background Technology

[0002] As a key auxiliary material in lithium-ion batteries, copper foil not only serves to support the negative electrode active material but also collects and transmits anode electron flow. Therefore, the rapid development of lithium-ion batteries has driven the rapid growth in demand for copper foil. However, against the backdrop of energy transition and the upgrading of electrical devices, it is necessary to further improve the energy density and safety of batteries. Theoretically, the use of silicon-carbon anode materials can significantly improve the energy density of the negative electrode active material.

[0003] During the cyclic charging and discharging process, lithium batteries not only generate a large amount of heat, but the silicon-carbon anode active material also undergoes significant volume changes, leading to abnormalities such as active material shedding and current collector breakage. This not only reduces the battery's energy density and cycle performance but may also cause thermal runaway and fire. Therefore, copper foil, as a carrier for lithium battery anode materials, needs to possess higher mechanical strength and stability.

[0004] Conventional copper foil suffers from several drawbacks. Firstly, its high warpage and low physical properties (warpage > 10mm, tensile strength 300-500MPa) negatively impact the uniformity and adhesion of the negative electrode active material coating, and it is prone to folding. Secondly, insufficient tensile strength leads to breakage, affecting process efficiency. Thirdly, during annealing to reduce warpage or in high-temperature environments, the stress in conventional copper foil is released, causing a decrease in tensile strength. These characteristics not only reduce battery manufacturing efficiency and increase costs, but also make the internal electrodes prone to breakage during battery cycling, resulting in reduced energy density, decreased cycle performance, and increased safety risks. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide a low-warpage ultra-high performance lithium battery copper foil, its preparation method and application. The copper foil can effectively reduce the risk of electrode folding and strip breakage, and improve the electrode manufacturing process efficiency.

[0006] This invention provides a low-warpage, ultra-high-performance lithium-ion battery copper foil, the copper foil comprising a smooth surface and a rough surface, wherein the warpage direction of the copper foil is from the smooth surface to the rough surface, and the warpage is <10 mm.

[0007] Preferably, the tensile strength of the copper foil decreases by less than 8% after baking at 150°C for 160 min.

[0008] Preferably, the copper foil has a thickness of 3-15 μm, a tensile strength of 600-700 MPa, and an elongation of >3%.

[0009] This invention also provides a method for preparing low-warpage ultra-high performance lithium-ion battery copper foil, wherein the copper foil is prepared by electrolysis; wherein the electrolysis system includes 85g / L-95g / L of copper ions, 110g / L-130g / L of sulfuric acid, 10-40ppm of chloride ions, and 10-180ppm of organic composite foil-forming agent; the organic composite foil-forming agent, by weight, includes 30-100 parts of organic sulfide, 5-15 parts of gelatin, 5-20 parts of polyethylene glycol, 1-10 parts of collagen, 10-20 parts of nitrogen-containing compound, and 5-20 parts of polyether compound.

[0010] Preferably, the organic sulfide includes one or more of 3-mercaptopropane sulfonate, bis-(3-sulfopropyl)-disulfide, bis-(sulfoethyl sodium)-disulfide, dimethyl sulfoxide, 2-methyl-2-thiazoline, 2-mercaptothiazoline, and alcohol thiopropane sulfonate.

[0011] Preferably, the nitrogen-containing compound includes one or more of polyethyleneimine, ethoxylated polyethyleneimine, N,N-dimethylformamide, and polyacrylamide.

[0012] Preferably, the polyether compound includes one or more of octylphenol polyoxyethylene ether, polyether acrylate, and polyether thiol.

[0013] Preferably, the electrolysis process parameters are: electrolysis temperature of 45~60℃, and current applied during electrolysis of 10000A-70000A.

[0014] The present invention also provides an application of low-warpage ultra-high performance lithium-ion battery copper foil in electrical devices, including current collectors, electrodes, and batteries.

[0015] The key point of this invention is that it provides a low-warpage, ultra-high-performance lithium-ion battery copper foil with a warpage of <10mm on both the smooth and rough surfaces. Because the smooth surface has smaller and more numerous grains than the rough surface, and more grain boundaries, while residual stress mainly exists at these grain boundaries, the stress on the smooth surface is greater than that on the rough surface, thus exhibiting warpage between the smooth and rough surfaces. This low-warpage copper foil not only has a small difference in stress between the smooth and rough surfaces, stable performance, and is less prone to folding during winding and unwinding, but also makes it easier to control the uniformity of the coating slurry and improve the adhesion between the negative electrode material and the current collector during the lithium-ion battery coating process, reducing the probability of electrode folding and improving the efficiency of the negative electrode manufacturing process.

[0016] The second key point of this invention is to provide a low-warpage, ultra-high-performance lithium-ion battery copper foil, which exhibits a tensile strength decrease of less than 8% after baking at 150°C for 160 minutes. This copper foil possesses a uniform and refined grain structure with an average grain size of 0.3-0.4 μm and a twinning ratio of 50-70%. These grain characteristics not only improve the tensile strength and ductility of the copper foil itself but also ensure its strength and thermal stability under high-temperature conditions, thereby enhancing the high stability and safety of batteries, especially silicon-carbon anode batteries, under high-temperature cycling.

[0017] The third key point of this invention is the provision of a low-warpage, ultra-high-performance lithium-ion battery copper foil with a thickness of 3-15 μm, a tensile strength of 600-700 MPa, and an elongation >3%. This copper foil not only has an extremely thin thickness but also possesses ultra-high tensile strength and elongation. Thinner copper foil means lighter weight and lower resistance. From a battery perspective, using thinner copper foil further improves the battery's energy density and safety, while also effectively reducing raw material costs. The ultra-high tensile strength and elongation mean that more negative electrode material can be coated on the copper foil surface and that it can tolerate active materials with higher expansion coefficients, increasing electrode compaction density and battery energy density, and reducing the risk of electrode breakage.

[0018] The fourth key point of this invention is to provide a method for preparing low-warpage, ultra-high-performance lithium-ion battery copper foil, specifically an organic composite foil-forming agent. This organic composite foil-forming agent, by proportioning organic sulfides (brighteners) and nitrogen-containing compounds (leveling agents), makes the crystal structure of the copper foil more flat and dense, generating a large number of nanocrystalline regions, fully utilizing the theoretical principles of grain refinement and increasing the proportion of nanotwins. The excellent structural interaction between fine grains and nanotwins increases both the tensile strength and elongation of the copper foil. Similarly, this organic composite foil-forming agent also includes polyethylene glycol as a leveling agent. The mechanism of action of the leveling agent is to adsorb onto the copper crystal growth surface and form a barrier layer. This barrier layer slows down the diffusion rate and growth speed of copper ions on the crystal surface, causing the grain shape to tend towards equiaxed shape, and the higher the molecular weight of the leveling agent, the stronger the inhibitory effect on grain growth.

[0019] The fifth key point of this invention is a current collector that has the advantages of the lithium-ion battery copper foil described in this invention. It has low warpage and ultra-high performance, which reduces breakage and folding during winding, unwinding, cell manufacturing, and use, thereby improving production efficiency and enhancing battery cycle life and safety.

[0020] The sixth key point of this invention is that the electrode sheet has the advantages of the lithium battery copper foil described in this invention. It has low warpage and ultra-high performance, can have more coating material and higher compaction density, improve battery energy density and extend battery life, and improve battery safety.

[0021] The seventh key point of this invention is that the battery has the advantages of the lithium-ion copper foil described in this invention, such as higher energy density, cycle life and safety.

[0022] Beneficial effects (1) Improve electrode manufacturing efficiency: The low warpage ultra-high performance lithium battery copper foil of the present invention can effectively reduce the risk of electrode folding and strip breakage, and improve electrode manufacturing efficiency.

[0023] (2) Enhanced battery thermal stability: The low warpage ultra-high performance lithium battery copper foil of the present invention can resist the high temperature and volume change generated by the battery during the cycle charging and discharging process, maintain stable physical properties, and thus improve the thermal stability of the battery.

[0024] (3) Improve battery energy density: With the optimization and iteration of negative electrode active materials, the low warp ultra-high performance lithium battery copper foil of the present invention can adapt to battery designs with higher energy density and compaction density, thereby improving battery energy density.

[0025] (4) Improve battery safety: Under extreme conditions such as impact or puncture, the low warpage ultra-high performance lithium battery copper foil of the present invention can effectively reduce the risk of electrode breakage and short circuit, and improve the battery safety factor.

[0026] (5) Extending battery cycle life: The low warpage ultra-high performance lithium battery copper foil of the present invention can maintain thermal stability during the battery cycle charging and discharging process, reduce the shedding of coating materials, and extend the battery cycle life. Attached Figure Description

[0027] Figure 1 The image shows the EBSD diagram of the low-warpage ultra-high performance lithium-ion battery copper foil prepared in Example 2.

[0028] Figure 2 The warp detection diagram is for the low-warp ultra-high performance lithium battery copper foil prepared in Example 6.

[0029] Figure 3 The image shows the EBSD pattern of the lithium-ion battery copper foil prepared in Comparative Example 1. Detailed Implementation

[0030] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0031] The testing method is as follows: ① The crystal structures of the samples in each embodiment and comparative example were observed and characterized using a C-Swift EBSD detector manufactured by Oxford Instruments, UK. To clearly observe the grain boundary contours of the samples, the cross-sections were polished for 20 minutes using an ion mill beforehand, and then the microcrystalline structure of the cross-sections was observed at a field of view of 3000.

[0032] ② Tensile strength and elongation: According to test method GB / T29847-2013, the tensile strength and elongation of the samples were tested using a HY-0230 universal testing machine manufactured by Shanghai Hengyi Precision Instruments Co., Ltd., at room temperature and a strain rate of 50 mm / min. The tensile test specimens were strip specimens with a 50 mm distance between the clamps. The samples were measured five times, and the average value was taken as the final tensile strength and elongation of the sample.

[0033] ③ Thermal stability test: Gradient baking was performed using a PHH-102M drying oven manufactured by ESPEC CORP, Japan. The temperature was first increased to 150℃ for 35 minutes and held for 160 minutes, followed by a cooling to room temperature (25℃) for 180 minutes. Similarly, the tensile strength and elongation were tested according to the method described in ②, and the difference in physical properties before and after the test was compared to confirm the thermal stability.

[0034] ④ Warpage test: Take a 300mm wide copper foil, use a disc sampler to cut three samples (left, middle, and right), place them on a hard, flat table with the rough side facing up, use a steel ruler to gently lift around the circumference of the copper foil, select the point of highest warpage, and use a steel ruler to test the warpage of the copper foil. Read the data and take the highest value as the warpage value.

[0035] Example 1 Copper wire with a purity of ≥99.5% and sulfuric acid are added to a copper melting vessel, and high-temperature air is blown in to prepare copper sulfate stock solution. The stock solution is then filtered through a diatomaceous earth filter, a security filter, and a precision filter. It is then mixed with an organic composite foil agent and hydrochloric acid to form a copper sulfate electrolyte. The copper sulfate electrolyte is heated to 50°C using a plate heat exchanger, and then discharged at a flow rate of 40m... 3 The copper sulfate electrolyte is injected into the electrolytic cell at a rate of / H, forming an electrolytic system consisting of a cathode roller with a titanium roller surface and an anode plate made of insoluble material, under a current of 35000A. The copper sulfate electrolyte contains 95 g / L of Cu. 2+The solution contained 115 g / L sulfuric acid, 25 ppm chloride ions, and 25 ppm organic composite foil-forming agent. By weight, the organic composite foil-forming agent comprised 46 parts 3-mercaptopropane sulfonate, 8 parts gelatin (molecular weight 50,000-60,000), 8 parts polyethylene glycol, 10 parts ethoxylated polyethyleneimine, 5 parts octylphenol polyoxyethylene ether, and 3 parts collagen. After roll forming, the foil was peeled, passivated for oxidation prevention, dried, and wound into raw foil. After annealing and slitting, it could be used as lithium-ion battery copper foil. Five full-width raw foil samples were baked at 150℃ for 10 min and 150℃ for 160 min, respectively, and then subjected to room temperature and high temperature tensile strength and elongation tests. The test results are shown in Table 1.

[0036] By weight, 91 parts of silicon-carbon anode active material, 6 parts of conductive carbon black, 2.0 parts of styrene-butadiene rubber (SBR), 1.0 parts of carboxymethyl cellulose (CMC), and 210 parts of deionized water were mixed to form a slurry. This slurry was then transferred and coated onto both surfaces of a copper foil. After gradient drying and rolling, the slurry was cut into anode sheets and wound together with the anode sheets and separator to form a core. Following assembly, sealing, electrolyte injection, activation, formation, secondary electrolyte replenishment, sealing, room temperature aging, and capacity testing, a 55Ah square battery was obtained. Finally, 10 square batteries were subjected to a 4.2V charging voltage and a 2.8V discharging voltage, 1C charging at room temperature and 2C discharging at 5000 charge-discharge cycles. The batteries were then disassembled in empty state to observe the electrode material detachment and breakage.

[0037] Example 2 Copper wire with a purity of ≥99.5% and sulfuric acid are added to a copper melting vessel, and high-temperature air is blown in to prepare copper sulfate stock solution. The stock solution is then filtered through a diatomaceous earth filter, a security filter, and a precision filter. It is then mixed with an organic composite foil agent and hydrochloric acid to form a copper sulfate electrolyte. The copper sulfate electrolyte is heated to 50°C using a plate heat exchanger, and then discharged at a flow rate of 40m... 3 The copper sulfate electrolyte is injected into the electrolytic cell at a rate of / H, forming an electrolytic system consisting of a cathode roller with a titanium roller surface and an anode plate made of insoluble material, under a current of 35000A. The copper sulfate electrolyte contains 95 g / L of Cu. 2+The solution contained 115 g / L of sulfuric acid, 25 ppm of chloride ions, and 25 ppm of an organic composite foil-forming agent. By weight, the organic composite foil-forming agent comprised 45 parts 3-mercaptopropane sulfonate, 45 parts bis-(3-sulfopropyl)-disulfide, 8 parts gelatin (molecular weight 50,000-60,000), 8 parts polyethylene glycol, 10 parts ethoxylated polyethyleneimine, 5 parts octylphenol polyoxyethylene ether, and 3 parts collagen. After roll forming, the foil was peeled, passivated for oxidation prevention, dried, and wound into raw foil. After annealing and slitting, it could be used as lithium-ion battery copper foil. Five full-width raw foil samples were baked at 150℃ for 10 min and 150℃ for 160 min, respectively, and then subjected to room temperature and high temperature tensile strength and elongation tests. The test results are shown in Table 1.

[0038] By weight, 91 parts of silicon-carbon anode active material, 6 parts of conductive carbon black, 2.0 parts of styrene-butadiene rubber (SBR), 1.0 parts of carboxymethyl cellulose (CMC), and 210 parts of deionized water were mixed to form a slurry. This slurry was then transferred and coated onto both surfaces of a copper foil. After gradient drying and rolling, the slurry was cut into anode sheets and wound together with the anode sheets and separator to form a core. Following assembly, sealing, electrolyte injection, activation, formation, secondary electrolyte replenishment, sealing, room temperature aging, and capacity testing, a 55Ah square battery was obtained. Finally, 10 square batteries were subjected to a 4.2V charging voltage and a 2.8V discharging voltage, 1C charging at room temperature and 2C discharging at 5000 charge-discharge cycles. The batteries were then disassembled in empty state to observe the electrode material detachment and breakage.

[0039] Example 3 Copper wire with a purity of ≥99.5% and sulfuric acid are added to a copper melting vessel, and high-temperature air is blown in to prepare copper sulfate stock solution. The stock solution is then filtered through a diatomaceous earth filter, a security filter, and a precision filter. It is then mixed with an organic composite foil agent and hydrochloric acid to form a copper sulfate electrolyte. The copper sulfate electrolyte is heated to 50°C using a plate heat exchanger, and then discharged at a flow rate of 40m... 3 The copper sulfate electrolyte is injected into the electrolytic cell at a rate of / H, forming an electrolytic system consisting of a cathode roller with a titanium roller surface and an anode plate made of insoluble material, under a current of 35000A. The copper sulfate electrolyte contains 95 g / L of Cu. 2+The solution contained 115 g / L sulfuric acid, 25 ppm chloride ions, and 25 ppm organic composite foil-forming agent. By weight, the organic composite foil-forming agent comprised 45 parts 3-mercaptopropane sulfonate, 45 parts 2-mercaptothiazoline, 8 parts gelatin (molecular weight 50,000-60,000), 8 parts polyethylene glycol, 10 parts ethoxylated polyethyleneimine, 8 parts octylphenol polyoxyethylene ether, and 3 parts collagen. After roll forming, the foil was peeled, passivated for oxidation prevention, dried, and wound into raw foil. After annealing and slitting, it could be used as lithium-ion battery copper foil. Five full-width raw foil samples were baked at 150℃ for 10 min and 150℃ for 160 min, respectively, and then subjected to room temperature and high temperature tensile strength and elongation tests. The test results are shown in Table 1.

[0040] By weight, 91 parts of silicon-carbon anode active material, 6 parts of conductive carbon black, 2.0 parts of styrene-butadiene rubber (SBR), 1.0 parts of carboxymethyl cellulose (CMC), and 210 parts of deionized water were mixed to form a slurry. This slurry was then transferred and coated onto both surfaces of a copper foil. After gradient drying and rolling, the slurry was cut into anode sheets and wound together with the anode sheets and separator to form a core. Following assembly, sealing, electrolyte injection, activation, formation, secondary electrolyte replenishment, sealing, room temperature aging, and capacity testing, a 55Ah square battery was obtained. Finally, 10 square batteries were subjected to a 4.2V charging voltage and a 2.8V discharging voltage, 1C charging at room temperature and 2C discharging at 5000 charge-discharge cycles. The batteries were then disassembled in empty state to observe the electrode material detachment and breakage.

[0041] Example 4 Copper wire with a purity of ≥99.5% and sulfuric acid are added to a copper melting vessel, and high-temperature air is blown in to prepare copper sulfate stock solution. The stock solution is then filtered through a diatomaceous earth filter, a security filter, and a precision filter. It is then mixed with an organic composite foil agent and hydrochloric acid to form a copper sulfate electrolyte. The copper sulfate electrolyte is heated to 50°C using a plate heat exchanger, and then discharged at a flow rate of 40m... 3 The copper sulfate electrolyte is injected into the electrolytic cell at a rate of / H, forming an electrolytic system consisting of a cathode roller with a titanium roller surface and an anode plate made of insoluble material, under a current of 35000A. The copper sulfate electrolyte contains 95 g / L of Cu. 2+The solution contained 115 g / L of sulfuric acid, 25 ppm of chloride ions, and 25 ppm of an organic composite foil-forming agent. By weight, the organic composite foil-forming agent comprised 45 parts 3-mercaptopropane sulfonate, 45 parts 3-N,N-dimethylaminodithiocarbamoyl-1-propanesulfonic acid, 8 parts gelatin (molecular weight 50,000-60,000), 8 parts polyethylene glycol, 10 parts ethoxylated polyethyleneimine, 5 parts octylphenol polyoxyethylene ether, and 3 parts collagen. After roll forming, the foil was peeled, passivated for oxidation prevention, dried, and wound into a raw foil. After annealing and slitting, it could be used as lithium-ion battery copper foil. Five full-width raw foil samples were baked at 150℃ for 10 min and 150℃ for 160 min, respectively, and then subjected to room temperature and high temperature tensile strength and elongation tests. The test results are shown in Table 1.

[0042] By weight, 91 parts of silicon-carbon anode active material, 6 parts of conductive carbon black, 2.0 parts of styrene-butadiene rubber (SBR), 1.0 parts of carboxymethyl cellulose (CMC), and 210 parts of deionized water were mixed to form a slurry. This slurry was then transferred and coated onto both surfaces of a copper foil. After gradient drying and rolling, the slurry was cut into anode sheets and wound together with the anode sheets and separator to form a core. Following assembly, sealing, electrolyte injection, activation, formation, secondary electrolyte replenishment, sealing, room temperature aging, and capacity testing, a 55Ah square battery was obtained. Finally, 10 square batteries were subjected to a 4.2V charging voltage and a 2.8V discharging voltage, 1C charging at room temperature and 2C discharging at 5000 charge-discharge cycles. The batteries were then disassembled in empty state to observe the electrode material detachment and breakage.

[0043] Example 5 Copper wire with a purity of ≥99.5% and sulfuric acid are added to a copper melting vessel, and high-temperature air is blown in to prepare copper sulfate stock solution. The stock solution is then filtered through a diatomaceous earth filter, a security filter, and a precision filter. It is then mixed with an organic composite foil agent and hydrochloric acid to form a copper sulfate electrolyte. The copper sulfate electrolyte is heated to 50°C using a plate heat exchanger, and then discharged at a flow rate of 40m... 3 The copper sulfate electrolyte is injected into the electrolytic cell at a rate of / H, forming an electrolytic system consisting of a cathode roller with a titanium roller surface and an anode plate made of insoluble material, under a current of 35000A. The copper sulfate electrolyte contains 95 g / L of Cu. 2+The solution contained 115 g / L sulfuric acid, 25 ppm chloride ions, and 25 ppm organic composite foil-forming agent. By weight, the organic composite foil-forming agent comprised 45 parts 3-mercaptopropane sulfonate, 45 parts formyl-1-propanesulfonic acid, 8 parts gelatin (molecular weight 50,000-60,000), 8 parts polyethylene glycol, 10 parts ethoxylated polyethyleneimine, 5 parts octylphenol polyoxyethylene ether, and 3 parts collagen. After roll forming, the foil was peeled, passivated for oxidation prevention, dried, and wound into raw foil. After annealing and slitting, it could be used as lithium-ion battery copper foil. Five full-width raw foil samples were baked at 150℃ for 10 min and 150℃ for 160 min, respectively, and then subjected to room temperature and high temperature tensile strength and elongation tests. The test results are shown in Table 1.

[0044] By weight, 91 parts of silicon-carbon anode active material, 6 parts of conductive carbon black, 2.0 parts of styrene-butadiene rubber (SBR), 1.0 parts of carboxymethyl cellulose (CMC), and 210 parts of deionized water were mixed to form a slurry. This slurry was then transferred and coated onto both surfaces of a copper foil. After gradient drying and rolling, the slurry was cut into anode sheets and wound together with the anode sheets and separator to form a core. Following assembly, sealing, electrolyte injection, activation, formation, secondary electrolyte replenishment, sealing, room temperature aging, and capacity testing, a 55Ah square battery was obtained. Finally, 10 square batteries were subjected to a 4.2V charging voltage and a 2.8V discharging voltage, 1C charging at room temperature and 2C discharging at 5000 charge-discharge cycles. The batteries were then disassembled in empty state to observe the electrode material detachment and breakage.

[0045] Example 6 Copper wire with a purity of ≥99.5% and sulfuric acid are added to a copper melting vessel, and high-temperature air is blown in to prepare copper sulfate stock solution. The stock solution is then filtered through a diatomaceous earth filter, a security filter, and a precision filter. It is then mixed with an organic composite foil agent and hydrochloric acid to form a copper sulfate electrolyte. The copper sulfate electrolyte is heated to 50°C using a plate heat exchanger, and then discharged at a flow rate of 40m... 3 The copper sulfate electrolyte is injected into the electrolytic cell at a rate of / H, forming an electrolytic system consisting of a cathode roller with a titanium roller surface and an anode plate made of insoluble material, under a current of 35000A. The copper sulfate electrolyte contains 95 g / L of Cu. 2+The solution contains 115 g / L sulfuric acid, 25 ppm chloride ions, and 25 ppm organic composite foil-forming agent. By weight, the organic composite foil-forming agent comprises 15 parts 3-mercaptopropane sulfonate, 15 parts 3-N,N-dimethylaminodithiocarbamoyl-1-propanesulfonic acid, 8 parts gelatin (molecular weight 50,000-60,000), 8 parts polyethylene glycol, 10 parts ethoxylated polyethyleneimine, 10 parts polyether dithiol, and 3 parts collagen. After roll forming, the foil is peeled, passivated for oxidation prevention, dried, and wound into raw foil. After annealing and slitting, it can be used as lithium battery copper foil. Five full-width raw foil samples were baked at 150℃ for 10 min and 150℃ for 160 min, respectively, and then subjected to room temperature and high temperature tensile strength and elongation tests. The test results are shown in Table 1.

[0046] By weight, 91 parts of silicon-carbon anode active material, 6 parts of conductive carbon black, 2.0 parts of styrene-butadiene rubber (SBR), 1.0 parts of carboxymethyl cellulose (CMC), and 210 parts of deionized water were mixed to form a slurry. This slurry was then transferred and coated onto both surfaces of a copper foil. After gradient drying and rolling, the slurry was cut into anode sheets and wound together with the anode sheets and separator to form a core. Following assembly, sealing, electrolyte injection, activation, formation, secondary electrolyte replenishment, sealing, room temperature aging, and capacity testing, a 55Ah square battery was obtained. Finally, 10 square batteries were subjected to a 4.2V charging voltage and a 2.8V discharging voltage, 1C charging at room temperature and 2C discharging at 5000 charge-discharge cycles. The batteries were then disassembled in empty state to observe the electrode material detachment and breakage.

[0047] Example 7 Copper wire with a purity of ≥99.5% and sulfuric acid are added to a copper melting vessel, and high-temperature air is blown in to prepare copper sulfate stock solution. The stock solution is then filtered through a diatomaceous earth filter, a security filter, and a precision filter. It is then mixed with an organic composite foil agent and hydrochloric acid to form a copper sulfate electrolyte. The copper sulfate electrolyte is heated to 50°C using a plate heat exchanger, and then discharged at a flow rate of 40m... 3 The copper sulfate electrolyte is injected into the electrolytic cell at a rate of / H, forming an electrolytic system consisting of a cathode roller with a titanium roller surface and an anode plate made of insoluble material, under a current of 35000A. The copper sulfate electrolyte contains 95 g / L of Cu. 2+The solution contains 115 g / L sulfuric acid, 25 ppm chloride ions, and 25 ppm organic composite foil-forming agent. By weight, the organic composite foil-forming agent comprises 60 parts 3-mercaptopropane sulfonate, 60 parts 3-N,N-dimethylaminodithiocarbamoyl-1-propanesulfonic acid, 8 parts gelatin (molecular weight 50,000-60,000), 8 parts polyethylene glycol, 10 parts ethoxylated polyethyleneimine, 10 parts polyether dithiol, and 3 parts collagen. After roll forming, the foil is peeled, passivated for oxidation prevention, dried, and wound into a raw foil. After annealing and slitting, it can be used as lithium-ion battery copper foil. Five full-width raw foil samples were baked at 150℃ for 10 min and 150℃ for 160 min, respectively, and then subjected to room temperature and high temperature tensile strength and elongation tests. The test results are shown in Table 1.

[0048] By weight, 91 parts of silicon-carbon anode active material, 6 parts of conductive carbon black, 2.0 parts of styrene-butadiene rubber (SBR), 1.0 parts of carboxymethyl cellulose (CMC), and 210 parts of deionized water were mixed to form a slurry. This slurry was then transferred and coated onto both surfaces of a copper foil. After gradient drying and rolling, the slurry was cut into anode sheets and wound together with the anode sheets and separator to form a core. Following assembly, sealing, electrolyte injection, activation, formation, secondary electrolyte replenishment, sealing, room temperature aging, and capacity testing, a 55Ah square battery was obtained. Finally, 10 square batteries were subjected to a 4.2V charging voltage and a 2.8V discharging voltage, 1C charging at room temperature and 2C discharging at 5000 charge-discharge cycles. The batteries were then disassembled in empty state to observe the electrode material detachment and breakage.

[0049] Example 8 Copper wire with a purity of ≥99.5% and sulfuric acid are added to a copper melting vessel, and high-temperature air is blown in to prepare copper sulfate stock solution. The stock solution is then filtered through a diatomaceous earth filter, a security filter, and a precision filter. It is then mixed with an organic composite foil agent and hydrochloric acid to form a copper sulfate electrolyte. The copper sulfate electrolyte is heated to 50°C using a plate heat exchanger, and then discharged at a flow rate of 40m... 3 The copper sulfate electrolyte is injected into the electrolytic cell at a rate of / H, forming an electrolytic system consisting of a cathode roller with a titanium roller surface and an anode plate made of insoluble material, under a current of 35000A. The copper sulfate electrolyte contains 95 g / L of Cu. 2+The solution contains 115 g / L sulfuric acid, 25 ppm chloride ions, and 25 ppm organic composite foil-forming agent. By weight, the organic composite foil-forming agent comprises 45 parts 3-mercaptopropane sulfonate, 45 parts 3-N,N-dimethylaminodithiocarbamoyl-1-propanesulfonic acid, 5 parts gelatin (molecular weight 50,000-60,000), 8 parts polyethylene glycol, 10 parts ethoxylated polyethyleneimine, 10 parts polyether dithiol, and 3 parts collagen. After roll forming, the foil is peeled, passivated for oxidation prevention, dried, and wound into raw foil. After annealing and slitting, it can be used as lithium battery copper foil. Five full-width raw foil samples were baked at 150℃ for 10 min and 150℃ for 160 min, respectively, and then their room temperature and high temperature tensile strength and elongation were tested. The test results are shown in Table 1.

[0050] By weight, 91 parts of silicon-carbon anode active material, 6 parts of conductive carbon black, 2.0 parts of styrene-butadiene rubber (SBR), 1.0 parts of carboxymethyl cellulose (CMC), and 210 parts of deionized water were mixed to form a slurry. This slurry was then transferred and coated onto both surfaces of a copper foil. After gradient drying and rolling, the slurry was cut into anode sheets and wound together with the anode sheets and separator to form a core. Following assembly, sealing, electrolyte injection, activation, formation, secondary electrolyte replenishment, sealing, room temperature aging, and capacity testing, a 55Ah square battery was obtained. Finally, 10 square batteries were subjected to a 4.2V charging voltage and a 2.8V discharging voltage, 1C charging at room temperature and 2C discharging at 5000 charge-discharge cycles. The batteries were then disassembled in empty state to observe the electrode material detachment and breakage.

[0051] Example 9 Copper wire with a purity of ≥99.5% and sulfuric acid are added to a copper melting vessel, and high-temperature air is blown in to prepare copper sulfate stock solution. The stock solution is then filtered through a diatomaceous earth filter, a security filter, and a precision filter. It is then mixed with an organic composite foil agent and hydrochloric acid to form a copper sulfate electrolyte. The copper sulfate electrolyte is heated to 50°C using a plate heat exchanger, and then discharged at a flow rate of 40m... 3 The copper sulfate electrolyte is injected into the electrolytic cell at a rate of / H, forming an electrolytic system consisting of a cathode roller with a titanium roller surface and an anode plate made of insoluble material, under a current of 35000A. The copper sulfate electrolyte contains 95 g / L of Cu. 2+The solution contains 115 g / L sulfuric acid, 25 ppm chloride ions, and 25 ppm organic composite foil-forming agent. By weight, the organic composite foil-forming agent comprises 45 parts 3-mercaptopropane sulfonate, 45 parts 3-N,N-dimethylaminodithiocarbamoyl-1-propanesulfonic acid, 10 parts gelatin (molecular weight 50,000-60,000), 8 parts polyethylene glycol, 10 parts ethoxylated polyethyleneimine, 12 parts polyether dithiol, and 5 parts collagen. After roll forming, the foil is peeled, passivated for oxidation prevention, dried, and wound into raw foil. After annealing and slitting, it can be used as lithium-ion battery copper foil. Five full-width raw foil samples were baked at 150℃ for 10 min and 150℃ for 160 min, respectively, and then subjected to room temperature and high temperature tensile strength and elongation tests. The test results are shown in Table 1.

[0052] By weight, 91 parts of silicon-carbon anode active material, 6 parts of conductive carbon black, 2.0 parts of styrene-butadiene rubber (SBR), 1.0 parts of carboxymethyl cellulose (CMC), and 210 parts of deionized water were mixed to form a slurry. This slurry was then transferred and coated onto both surfaces of a copper foil. After gradient drying and rolling, the slurry was cut into anode sheets and wound together with the anode sheets and separator to form a core. Following assembly, sealing, electrolyte injection, activation, formation, secondary electrolyte replenishment, sealing, room temperature aging, and capacity testing, a 55Ah square battery was obtained. Finally, 10 square batteries were subjected to a 4.2V charging voltage and a 2.8V discharging voltage, 1C charging at room temperature and 2C discharging at 5000 charge-discharge cycles. The batteries were then disassembled in empty state to observe the electrode material detachment and breakage.

[0053] Example 10 Copper wire with a purity of ≥99.5% and sulfuric acid are added to a copper melting vessel, and high-temperature air is blown in to prepare copper sulfate stock solution. The stock solution is then filtered through a diatomaceous earth filter, a security filter, and a precision filter. It is then mixed with an organic composite foil agent and hydrochloric acid to form a copper sulfate electrolyte. The copper sulfate electrolyte is heated to 50°C using a plate heat exchanger, and then discharged at a flow rate of 40m... 3 The copper sulfate electrolyte is injected into the electrolytic cell at a rate of / H, forming an electrolytic system consisting of a cathode roller with a titanium roller surface and an anode plate made of insoluble material, under a current of 35000A. The copper sulfate electrolyte contains 95 g / L of Cu. 2+The solution contained 115 g / L of sulfuric acid, 25 ppm of chloride ions, and 25 ppm of an organic composite foil-forming agent. By weight, the organic composite foil-forming agent comprised 45 parts 3-mercaptopropane sulfonate, 45 parts 3-N,N-dimethylaminodithiocarbamoyl-1-propanesulfonic acid, 8 parts gelatin (molecular weight 30,000-40,000), 8 parts polyethylene glycol, 10 parts ethoxylated polyethyleneimine, 8 parts polyether dithiol, and 3 parts collagen. After roll forming, the foil was peeled, passivated for oxidation prevention, dried, and wound into a raw foil. After annealing and slitting, it could be used as lithium-ion battery copper foil. Five full-width raw foil samples were baked at 150℃ for 10 min and 150℃ for 160 min, respectively, and then subjected to room temperature and high temperature tensile strength and elongation tests. The test results are shown in Table 1.

[0054] By weight, 91 parts of silicon-carbon anode active material, 6 parts of conductive carbon black, 2.0 parts of styrene-butadiene rubber (SBR), 1.0 parts of carboxymethyl cellulose (CMC), and 210 parts of deionized water were mixed to form a slurry. This slurry was then transferred and coated onto both surfaces of a copper foil. After gradient drying and rolling, the slurry was cut into anode sheets and wound together with the anode sheets and separator to form a core. Following assembly, sealing, electrolyte injection, activation, formation, secondary electrolyte replenishment, sealing, room temperature aging, and capacity testing, a 55Ah square battery was obtained. Finally, 10 square batteries were subjected to a 4.2V charging voltage and a 2.8V discharging voltage, 1C charging at room temperature and 2C discharging at 5000 charge-discharge cycles. The batteries were then disassembled in empty state to observe the electrode material detachment and breakage.

[0055] Comparative Example 1 Copper wire with a purity of ≥99.5% and sulfuric acid are added to a copper melting vessel, and high-temperature air is blown in to prepare copper sulfate stock solution. The stock solution is then filtered through a diatomaceous earth filter, a security filter, and a precision filter. It is then mixed with an organic composite foil agent and hydrochloric acid to form a copper sulfate electrolyte. The copper sulfate electrolyte is heated to 50°C using a plate heat exchanger, and then discharged at a flow rate of 40m... 3 The copper sulfate electrolyte is injected into the electrolytic cell at a rate of / H, forming an electrolytic system consisting of a cathode roller with a titanium roller surface and an anode plate made of insoluble material, under a current of 35000A. The copper sulfate electrolyte contains 95 g / L of Cu. 2+The solution contained 115 g / L of sulfuric acid, 25 ppm of chloride ions, and 25 ppm of an organic composite foil-forming agent. By weight, the organic composite foil-forming agent comprised 45 parts 2-methyl-2-thiazoline, 8 parts gelatin (molecular weight 50,000-60,000), 8 parts polyethylene glycol, 10 parts ethoxylated polyethyleneimine, and 12 parts collagen. After roll forming, the foil was peeled, passivated for oxidation prevention, dried, and wound into raw foil. After annealing and slitting, it could be used as lithium-ion battery copper foil. Five full-width raw foil samples were baked at 150℃ for 10 min and 150℃ for 160 min, respectively, and then subjected to room temperature and high temperature tensile strength and elongation tests. The test results are shown in Table 1.

[0056] By weight, 91 parts of silicon-carbon anode active material, 6 parts of conductive carbon black, 2.0 parts of styrene-butadiene rubber (SBR), 1.0 parts of carboxymethyl cellulose (CMC), and 210 parts of deionized water were mixed to form a slurry. This slurry was then transferred and coated onto both surfaces of a copper foil. After gradient drying and rolling, the slurry was cut into anode sheets and wound together with the anode sheets and separator to form a core. After assembly, sealing, electrolyte injection, activation, formation, secondary electrolyte replenishment, sealing, room temperature aging, and capacity testing, a 55Ah square battery was obtained. Finally, 10 square batteries were subjected to a 4.2V charging voltage and a 2.8V discharging voltage, 1C charging and 2C discharging rate at room temperature, and 5000 charge-discharge cycles. The batteries were then disassembled to observe the electrode material detachment and breakage.

[0057] Comparative Example 2 Copper wire with a purity of ≥99.5% and sulfuric acid are added to a copper melting vessel, and high-temperature air is blown in to prepare copper sulfate stock solution. The stock solution is then filtered through a diatomaceous earth filter, a security filter, and a precision filter. It is then mixed with an organic composite foil agent and hydrochloric acid to form a copper sulfate electrolyte. The copper sulfate electrolyte is heated to 50°C using a plate heat exchanger, and then discharged at a flow rate of 40m... 3 The copper sulfate electrolyte is injected into the electrolytic cell at a rate of / H, forming an electrolytic system consisting of a cathode roller with a titanium roller surface and an anode plate made of insoluble material, under a current of 35000A. The copper sulfate electrolyte contains 95 g / L of Cu. 2+ The solution contained 115 g / L sulfuric acid, 25 ppm chloride ions, and 25 ppm organic composite foil-forming agent. By weight, the organic composite foil-forming agent comprised 45 parts 2-methyl sulfoxide, 8 parts gelatin (molecular weight 50,000-60,000), 4 parts polyethylene glycol, 10 parts ethoxylated polyethyleneimine, and 3 parts polyether dithiol. After roll forming, the foil was peeled, passivated for oxidation prevention, dried, and wound into raw foil. After annealing and slitting, it could be used as lithium-ion battery copper foil. Five full-width raw foil samples were baked at 150℃ for 10 min and 150℃ for 160 min, respectively, and then subjected to room temperature and high temperature tensile strength and elongation tests. The test results are shown in Table 1.

[0058] By weight, 91 parts of silicon-carbon anode active material, 6 parts of conductive carbon black, 2.0 parts of styrene-butadiene rubber (SBR), 1.0 parts of carboxymethyl cellulose (CMC), and 210 parts of deionized water were mixed to form a slurry. This slurry was then transferred and coated onto both surfaces of a copper foil. After gradient drying and rolling, the slurry was cut into anode sheets and wound together with the anode sheets and separator to form a core. Following assembly, sealing, electrolyte injection, activation, formation, secondary electrolyte replenishment, sealing, room temperature aging, and capacity testing, a 55Ah square battery was obtained. Finally, 10 square batteries were subjected to a 4.2V charging voltage and a 2.8V discharging voltage, 1C charging at room temperature and 2C discharging at 5000 charge-discharge cycles. The batteries were then disassembled in empty state to observe the electrode material detachment and breakage.

[0059] Comparative Example 3 Copper wire with a purity of ≥99.5% and sulfuric acid are added to a copper melting vessel, and high-temperature air is blown in to prepare copper sulfate stock solution. The stock solution is then filtered through a diatomaceous earth filter, a security filter, and a precision filter. It is then mixed with an organic composite foil agent and hydrochloric acid to form a copper sulfate electrolyte. The copper sulfate electrolyte is heated to 50°C using a plate heat exchanger, and then discharged at a flow rate of 40m... 3 The copper sulfate electrolyte is injected into the electrolytic cell at a rate of / H, forming an electrolytic system consisting of a cathode roller with a titanium roller surface and an anode plate made of insoluble material, under a current of 35000A. The copper sulfate electrolyte contains 95 g / L of Cu. 2+ The solution contains 115 g / L sulfuric acid, 25 ppm chloride ions, and 25 ppm organic composite foil-forming agent. By weight, the organic composite foil-forming agent comprises 45 parts thiopropane sulfonate, 8 parts gelatin (molecular weight 50,000-60,000), 8 parts polyethylene glycol, 8 parts ethoxylated polyethyleneimine, 8 parts polyether dithiol, and 13 parts collagen. After roll forming, the foil is peeled, passivated for oxidation prevention, dried, and wound into raw foil. After annealing and slitting, it can be used as lithium battery copper foil. Five full-width raw foil samples were baked at 150℃ for 10 min and 150℃ for 160 min, respectively, and then subjected to room temperature and high temperature tensile strength and elongation tests. The test results are shown in Table 1.

[0060] By weight, 91 parts of silicon-carbon anode active material, 6 parts of conductive carbon black, 2.0 parts of styrene-butadiene rubber (SBR), 1.0 parts of carboxymethyl cellulose (CMC), and 210 parts of deionized water were mixed to form a slurry. This slurry was then transferred and coated onto both surfaces of a copper foil. After gradient drying and rolling, the slurry was cut into anode sheets and wound together with the anode sheets and separator to form a core. Following assembly, sealing, electrolyte injection, activation, formation, secondary electrolyte replenishment, sealing, room temperature aging, and capacity testing, a 55Ah square battery was obtained. Finally, 10 square batteries were subjected to a 4.2V charging voltage and a 2.8V discharging voltage, 1C charging at room temperature and 2C discharging at 5000 charge-discharge cycles. The batteries were then disassembled in empty state to observe the electrode material detachment and breakage.

[0061] Comparative Example 4 Copper wire with a purity of ≥99.5% and sulfuric acid are added to a copper melting vessel, and high-temperature air is blown in to prepare copper sulfate stock solution. The stock solution is then filtered through a diatomaceous earth filter, a security filter, and a precision filter. It is then mixed with an organic composite foil agent and hydrochloric acid to form a copper sulfate electrolyte. The copper sulfate electrolyte is heated to 50°C using a plate heat exchanger, and then discharged at a flow rate of 40m... 3 The copper sulfate electrolyte is injected into the electrolytic cell at a rate of / H, forming an electrolytic system consisting of a cathode roller with a titanium roller surface and an anode plate made of insoluble material, under a current of 35000A. The copper sulfate electrolyte contains 95 g / L of Cu. 2+ The solution contains 115 g / L sulfuric acid, 25 ppm chloride ions, and 25 ppm organic composite foil-forming agent. By weight, the organic composite foil-forming agent comprises 10 parts 3-mercaptopropane sulfonate, 15 parts 3-N,N-dimethylaminodithiocyanate, 4 parts gelatin (molecular weight 50,000-60,000), 4 parts polyethylene glycol, 24 parts ethoxylated polyethyleneimine, and 4 parts polyether dithiol. After roll forming, the foil is peeled, passivated for oxidation prevention, dried, and wound into raw foil. After annealing and slitting, it can be used as lithium-ion battery copper foil. Five full-width raw foil samples were baked at 150℃ for 10 min and 150℃ for 160 min, respectively, and then their room temperature and high temperature tensile strength and elongation were tested. The test results are shown in Table 1.

[0062] By weight, 91 parts of silicon-carbon anode active material, 6 parts of conductive carbon black, 2.0 parts of styrene-butadiene rubber (SBR), 1.0 parts of carboxymethyl cellulose (CMC), and 210 parts of deionized water were mixed to form a slurry. This slurry was then transferred and coated onto both surfaces of a copper foil. After gradient drying and rolling, the slurry was cut into anode sheets and wound together with the anode sheets and separator to form a core. Following assembly, sealing, electrolyte injection, activation, formation, secondary electrolyte replenishment, sealing, room temperature aging, and capacity testing, a 55Ah square battery was obtained. Finally, 10 square batteries were subjected to a 4.2V charging voltage and a 2.8V discharging voltage, 1C charging at room temperature and 2C discharging at 5000 charge-discharge cycles. The batteries were then disassembled in empty state to observe the electrode material detachment and breakage.

[0063] Comparative Example 5 Copper wire with a purity of ≥99.5% and sulfuric acid are added to a copper melting vessel, and high-temperature air is blown in to prepare copper sulfate stock solution. The stock solution is then filtered through a diatomaceous earth filter, a security filter, and a precision filter. It is then mixed with an organic composite foil agent and hydrochloric acid to form a copper sulfate electrolyte. The copper sulfate electrolyte is heated to 50°C using a plate heat exchanger, and then discharged at a flow rate of 40m... 3 The copper sulfate electrolyte is injected into the electrolytic cell at a rate of / H, forming an electrolytic system consisting of a cathode roller with a titanium roller surface and an anode plate made of insoluble material, under a current of 35000A. The copper sulfate electrolyte contains 95 g / L of Cu.2+ The solution contained 115 g / L of sulfuric acid, 25 ppm of chloride ions, and 25 ppm of an organic composite foil-forming agent. By weight, the organic composite foil-forming agent comprised 65 parts 3-mercaptopropane sulfonate, 8 parts gelatin (molecular weight 50,000-60,000), 8 parts polyethylene glycol, 10 parts ethoxylated polyethyleneimine, and 55 parts bis-(sodium sulfoethyl)-disulfide. After roll forming, the foil was peeled, passivated for oxidation prevention, dried, and wound into raw foil. After annealing and slitting, it could be used as lithium-ion battery copper foil. Five full-width raw foil samples were baked at 150℃ for 10 min and 150℃ for 160 min, respectively, and then subjected to room temperature and high temperature tensile strength and elongation tests. The test results are shown in Table 1.

[0064] By weight, 91 parts of silicon-carbon anode active material, 6 parts of conductive carbon black, 2.0 parts of styrene-butadiene rubber (SBR), 1.0 parts of carboxymethyl cellulose (CMC), and 210 parts of deionized water were mixed to form a slurry. This slurry was then transferred and coated onto both surfaces of a copper foil. After gradient drying and rolling, the slurry was cut into anode sheets and wound together with the anode sheets and separator to form a core. Following assembly, sealing, electrolyte injection, activation, formation, secondary electrolyte replenishment, sealing, room temperature aging, and capacity testing, a 55Ah square battery was obtained. Finally, 10 square batteries were subjected to a 4.2V charging voltage and a 2.8V discharging voltage, 1C charging at room temperature and 2C discharging at 5000 charge-discharge cycles. The batteries were then disassembled in empty state to observe the electrode material detachment and breakage.

[0065] Table 1. Performance results of copper foils and electrodes prepared in each embodiment and comparative example.

[0066] like Figure 1 and Figure 3 As shown, the use of organic composite foil-forming agents makes the crystal structure of copper foil more flat and dense, and generates a large number of nanocrystalline regions. On the one hand, the excellent structural interaction between fine crystals and nanotwins results in small stress difference between smooth and rough surfaces, low warpage, and stable performance, which increases the tensile strength of copper foil while also increasing its elongation. On the other hand, the current collector with low warpage and ultra-high performance makes it easier to control the uniformity of the coating slurry and improve the adhesion between the negative electrode material and the current collector during the lithium battery coating process, reducing the probability of electrode folding and improving the efficiency of the negative electrode process.

[0067] As shown in Table 1, the amount of composite foil-forming agent used in the comparative example is not within the scope of the claims. The grain size and structure of the smooth and rough surfaces are significantly different, the internal stress difference is large, the warpage is high, and its mechanical strength cannot reach ultra-high performance. Moreover, its strength stability in high temperature environment is poor. It is easy to break and detach the active material during the cell manufacturing process, and there is even a risk of thermal runaway during the high temperature cycle charging process of the battery.

Claims

1. A low-warpage, ultra-high-performance lithium-ion battery copper foil, characterized in that: The copper foil includes a smooth surface and a rough surface, and the warping direction of the copper foil is from the smooth surface to the rough surface, with a warping degree of <10 mm.

2. The low-warpage ultra-high performance lithium-ion battery copper foil according to claim 1, characterized in that: The tensile strength of the copper foil decreased by less than 8% after baking at 150°C for 160 min.

3. The low-warpage ultra-high performance lithium-ion battery copper foil according to claim 1, characterized in that: The copper foil has a thickness of 3-15 μm, a tensile strength of 600-700 MPa, and an elongation of >3%.

4. A method for preparing low-warpage ultra-high performance lithium-ion battery copper foil as described in claim 1, characterized in that: The copper foil is prepared by electrolysis; wherein the electrolysis system includes 85g / L-95g / L copper ions, 110g / L-130g / L sulfuric acid, 10-40ppm chloride ions, and 10-180ppm organic composite foil-forming agent; the organic composite foil-forming agent, by weight, includes 30-100 parts of organic sulfide, 5-15 parts of gelatin, 5-20 parts of polyethylene glycol, 1-10 parts of collagen, 10-20 parts of nitrogen-containing compound, and 5-20 parts of polyether compound.

5. The preparation method according to claim 4, characterized in that: The organic sulfides include one or more of 3-mercaptopropane sulfonate, bis-(3-sulfopropyl)-disulfide, bis-(sulfoethyl sodium)-disulfide, dimethyl sulfoxide, 2-methyl-2-thiazoline, 2-mercaptothiazoline, and alcohol thiopropane sulfonate.

6. The preparation method according to claim 4, characterized in that: The nitrogen-containing compounds include one or more of polyethyleneimine, ethoxy polyethyleneimine, N,N-dimethylformamide, and polyacrylamide.

7. The preparation method according to claim 4, characterized in that: The polyether compounds include one or more of octylphenol polyoxyethylene ether, polyether acrylate, and polyether thiol.

8. The preparation method according to claim 4, characterized in that: The electrolysis process parameters are as follows: electrolysis temperature is 45~60℃, and the current applied during electrolysis is 10000A-70000A.

9. The application of the low-warpage ultra-high performance lithium-ion battery copper foil as described in claim 1 in electrical devices.